2007
DOI: 10.1292/jvms.69.915
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study and Gene Analysis of Canine Sterile Panniculitis

Abstract: ABSTRACT. In this study, a retrospective analysis was conducted to assess the current aspects and predisposing factors of canine sterile panniculitis. Miniature dachshund, neutered, and younger dogs appeared to be predisposed. In addition, histories of previous surgery and injection were associated in 46.5% of the cases, with several types of surgical suture materials used. About 88% of the dogs had multifocal lesions, frequently with signs of systemic illnesses. Whereas systemic immunosuppressive therapy was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
19
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 26 publications
5
19
0
1
Order By: Relevance
“…Relatively few cases have been reported in dogs, and the cause and pathogenesis of these conditions are unknown. Dogs with sterile pyogranulomatous inflammation are controlled mainly with systemic corticosteroid [14,15,18]. A recent study found that idiopathic sterile pyogranulomatous inflammation of epidural fat caused spinal cord compression in five Miniature Dachshunds [3].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Relatively few cases have been reported in dogs, and the cause and pathogenesis of these conditions are unknown. Dogs with sterile pyogranulomatous inflammation are controlled mainly with systemic corticosteroid [14,15,18]. A recent study found that idiopathic sterile pyogranulomatous inflammation of epidural fat caused spinal cord compression in five Miniature Dachshunds [3].…”
mentioning
confidence: 99%
“…These dogs had similar symptoms of intervertebral disk herniation (IVDH), including back pain, paresis, or paraplegia. The Miniature Dachshund is predisposed to sterile pyogranulomatous inflammation, as well as IVDH [17,18]. Idiopathic sterile pyogranulomatous inflammation of epidural fat may therefore be a cause of thoracolumbar myelopathy in dogs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…SNP is an idiopathic disorder 1,3–5 that is either primary in origin or associated with a variety of other illnesses, including pancreatic nodular hyperplasia, 6 pancreatic neoplasia, 7–9 pancreatitis, 10 and immunologic diseases such as rheumatoid arthritis 11 and systemic lupus erythematosus (SLE) 3 . Concurrent inflammation of fat in the abdomen, 12 epidural space, 13 and bone 7 can occur in dogs with SNP, as can other inflammatory conditions such as polyarthritis 7 .…”
mentioning
confidence: 99%